Adaptability and stability of popcorn populations related through selection cycles - Faria, Vinícius Ribeiro; Viana, José Marcelo Soriano; Mundim, Gabriel Borges; Silva, Admilson da Costa e; Câmara, Tassiano Maxwell Marinho (Pesquisa Agropecuaria Brasileira, 2011)
The objectives of this work were to estimate the adaptability and stability parameters of popcorn populations related through cycles of selection, to infer about the efficiency of the selection methods by which the populations were obtained and to assess the effects of selection on the parameters of adaptability and stability. Twenty-five populations and three commercial controls were evaluated in 14 trials carried out in the 2003/2004, 2004/2005, 2006/2007, 2008/2009 and 2009/2010 growing seasons, in seven locations. The experimental design used was randomized complete blocks with four replicates. The expansion volume, evaluated in a microwave oven and in the Metric Weight Volume Tester (MWVT), as well as grain yield were analyzed. The Eberhart & Russell adaptability and stability method was used. In general the initial and improved populations showed predictable performance in response to changes in the environment. Selection can cause changes in the adaptability and stability patterns, and the different selection strategies performed in order to obtain the populations showed similar efficiencies.